The impact of chemical additives on the process of biodegradation of oil products - Žukauskaitė, Audronė; Jakubauskaitė, Viktorija; Ambrazaitienė, Dalia; Zabukas, Vytenis; Paulauskienė, Tatjana (Journal of Environmental Engineering and Landscape Management, 2012)
Many modern technologies for treatment of soil polluted with oil products are developed through creation of new and efficient bio-agents that help to degrade oil products. Another trend in development of new technologies aims to speed up the growth of soil microorganisms, this way accelerating biodegradation of oil products without the help of introduced microorganisms. The biodegradation of diesel fuel and heavy fuel oil was tested in the soil using chemical additives (oxidizing agents). The tests aimed to ascertain the impact of H2O2, KMnO4 and MnSO4 on residual concentrations of heavy fuel oil and diesel fuel, and the total number of microorganism colonies, as well as the number of oil-oxidizing microorganism colonies in the soil. After the statistical analysis of the data obtained during the experiment, a statistically significant (p